Pengaruh Gaya Kepemimpinan Situasional dan Iklim Organiasi Terhadap Kinerja Pegawai pada Sekretariat Daerah Kabupaten Tulang Bawang - Ida Farida (e-JKPP, 2015)
Target in this research is : (1) Influence of Style of Leadership situasional of To Officer Performance of Secretariat of Regency Tulang Bawang , (2) Climate Influence Work To Officer Performance of Secretariat of Regency Tulang Bawang, (3) Style of Leadership of situasional and Climate Work to have an effect on to Officer Performance of Secretariat of Regency Tulang Bawang.Research Method which is according to researcher as according to this research method is use the this research type is explanatory sur vey. Research population as much 60 officer people of both for status of Public Servant of Civil and also energy honorer of Secretariat of Area of Regency Tulang Bawang. With the consideration sum up the population of a little and its spreading at one location, hence entire/all population amount made by sampel hence can be said that by this research use the saturated withdrawal sampel technique or census.Result of research indicate that there is influence signifikan, good of style of leadership of situasional and also organizational climate to officer performance of at Secretariat of Area of Regency Tulang Bawang. Result of data processing of menunjukan that variable of style of leadership situasional of equal to 67,00 gratuity of while organizational climate variable equal to 66,30 gratuity, while influence by bersama-sam between officer performance of Secretariat of Area of Regency Tulang Bawang , equal to 66,70 gratuity, the mentioned be at the good enough category, but not yet optimal. Is thereby happened by because variable there be still be other;dissimilar influencing but is not checked.